This “Mad, Mad, Mad” World of the Strange Headings of the Electronic Media - Казимянец, Елена Генриховна Генриховна (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English]The article discusses the so-called “strange” titles in the electronic media collected by Yury Uskov and that got wide spread on the Network. Modern consumers of information in the virtual space carry out the choice of text for reading mainly by headings, moreover, the users often read only the titles, making the certain picture of reality based on them. The trend of modern Internet websites is the desire to attract as many advertisers as possible, and this is possible when the website is visited by a large number of “readers”. Therefore, the headlines of the media should be “clickable”, which can be contributed by their unusual construction or their promise of a story about an extraordinary incident. The frame analysis of the perception of such titles is conducted in the article, their classification is offered from the point of view of its correlation with the content of the article, and the “picture of the world” created by them is characterized.
Keywords: Internet website, title (heading), picture of the world, frame analysis, virtual space